2011
DOI: 10.1007/s13213-011-0241-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon and nitrogen sources on the formation of sclerotia in Morchella spp.

Abstract: Cultural assays were used to compare the effect of various carbon (C) and nitrogen (N) sources on in vitro sclerotial formation and development, specifically in mycelial cultures of black and yellow morels (Morchella elata and Morchella crassipes, respectively). While different C and N sources supported abundant mycelia growth, these nutritional parameters also influenced sclerotial formation. Carbon sources such as ribose, cellobiose, galactose, xylose, sucrose and mannitol produced many (18-125) large-sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…In this study, the epigeal fructifications (ascocarps) of M. conica are usually appeared in late February or in early March when soil temperature warms to above 10°C and this is in accordance with previous reports (Kanwal and Reddy, 2012;Masaphy, 2010;Goldway et al, 2000;Pilz et al, 2007;Ower et al, 1986). A number of studies point out that obtaining sclerotia are a necessary part of the process for domestication of the genus and commercial production (Buscot, 1994).…”
Section: Results Of the Commercial Planting For M Conicasupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the epigeal fructifications (ascocarps) of M. conica are usually appeared in late February or in early March when soil temperature warms to above 10°C and this is in accordance with previous reports (Kanwal and Reddy, 2012;Masaphy, 2010;Goldway et al, 2000;Pilz et al, 2007;Ower et al, 1986). A number of studies point out that obtaining sclerotia are a necessary part of the process for domestication of the genus and commercial production (Buscot, 1994).…”
Section: Results Of the Commercial Planting For M Conicasupporting
confidence: 93%
“…In nature, morel fruiting body formation is associated with a broad range of environmental stress conditions, some of which have yet to be defined (Masaphy, 2010) and up to now, there is no report about morel fruiting bodyformation and yield is associated with microelements, such as ferric, zinc, copper, molybdenum, among others. However, many literatures reported that microelements influenced the sclerotial formation and morels are rich in trace elements in their fruit-body (Kanwal and Reddy, 2012;Kalač, 2010;Amir et al, 1995). Fe•EDDHA is usually used to correct iron chlorosis in Strategy I plant, because of its great stability and solubility at high pHs (Rojas et al, 2008) A B C D Figure 3.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional conditions, especially the C:N ratio, are critical factors affecting exudate formation in Metarhizium anisopliae ( Stefan et al, 2010 ). Carbon sources such as glucose, ribose, galactose, xylose, cellobiose, sucrose, sorbose, and mannitol are often supplied alone or in combination to pathogens to study the relationship between morphogenesis and nutritional factors ( Kanwal & Reddy, 2012 ; Budge & Whipps, 1991 ; Kuës, 2000 ). Previous studies have shown that various carbon and nitrogen sources result in differently sized sclerotia in Morchella spp.…”
Section: Introductionmentioning
confidence: 99%
“…It had been demonstrated that the sclerotia were important in morel life cycle [1]. The specific conditions of nutrition, humidity, pH, CO 2 , light and temperature should be met for sclerotial formation [2][3][4][5] and the morphological polymorphism (i.e. size, color, quantity and microstructure) of morel sclerotia were frequently found in different species, different strains of the same species and different single spore isolates from the same ascocarp [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%